2021
DOI: 10.26434/chemrxiv.14444315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SnO2 -SiO2 1D Core-Shell Nanowires Heterostructures for Selective Hydrogen Sensing

Abstract: SnO2 is one of the most employed n-type semiconducting metal oxide (SMOX) in chemo-resistive gas-sensing although it presents serious limitations due to a low selectivity. Herein, we introduce one-dimensional (1D) SnO2-SiO2 core-shell nanowires (CSNWs). SnO2 nanowires (NWs) are synthesized by vapor–liquid–solid deposition and the amorphous SiO2-shell layer with varying thicknesses (1.8-10.5 nm) was grown by atomic layer deposition (ALD). SiO2-coated SnO2 CSNWs show lower baseline conductance as compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The isothermal response transients and the response of all the sensors at 200 °C (the optimal working temperature) are shown in Figure c,d. CNT-NiO(200) and CNT-SnO 2 (50) CSHS show typical p- and n-type sensing responses related to their intrinsic cations and anions deficiencies, respectively. ,,,,, The thickness of the NiO shell was fixed to 5.5–6.5 nm (200 ALD cycles) since it has already been optimized in our previous study . Noticeably, at this thickness which is similar to the Debye length, λ D , the whole layer participates in the resistance modulation and the sensing response is maximized .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isothermal response transients and the response of all the sensors at 200 °C (the optimal working temperature) are shown in Figure c,d. CNT-NiO(200) and CNT-SnO 2 (50) CSHS show typical p- and n-type sensing responses related to their intrinsic cations and anions deficiencies, respectively. ,,,,, The thickness of the NiO shell was fixed to 5.5–6.5 nm (200 ALD cycles) since it has already been optimized in our previous study . Noticeably, at this thickness which is similar to the Debye length, λ D , the whole layer participates in the resistance modulation and the sensing response is maximized .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Indeed, the sensing responses of heterostructured materials discussed in the literature are very disparate and not always related to the p–n semiconductor heterojunction ,,, but could be limited to the core or the shell material. ,, For example, it was demonstrated that although depositing a second material conformally onto already contacted (core–core junctions) 1D SnO 2 nanowires (SnO 2 -core) or carbon nanotubes (CNTs-core) modifies both the width and the thickness of the depletion region at the interface, the sensing responses were exclusively attributed to the core materials. ,, In that case, the shell-layers modified the surface of the already fabricated devices without dramatically modifying the underlying transduction mechanism. ,,,,, Alternatively, a change in the order of device/geometry and materials fabrication (e.g., by adding shell–shell junctions to the core–shell heterojunction and omitting the direct core–core junction) could result in a response related to (i) the shell layer, (ii) the core axis, or (iii) the p–n interface. ,,, A study on CNT-NiO core–shell heterostructures (CSHS) demonstrated that the response was strongly related to the NiO shell . Indeed, when an insulating alumina buffer layer was introduced between the NiO shell and the CNT-core substrate, the transduction mechanism and the response were not affected, but only the baseline resistance of the device increased.…”
Section: Introductionmentioning
confidence: 99%
“…The hierarchical core–shell/yolk–shell/hollow (CS/YS/Ho) structure has been studied in depth because of the controllable structure and large specific surface area. 14–16 Therefore, they are widely used in sensing, 17 drug delivery, 18 photocatalysis/electrocatalysis, 19,20 and electrochemical energy storage. 21,22 The traditional strategy for the CS/YS/Ho structure is mainly focused on the template method and demands multiple synthesis steps.…”
Section: Introductionmentioning
confidence: 99%